Non-fired pellets for reduction and method for producing same

By adding high viscosity slag composition in non-fired pellets and using high LOI raw materials, the problems of pellet pulverization and clustering in solid reduction furnaces are solved, achieving more efficient operation and lower CO2 emissions.

CN119630820APending Publication Date: 2025-03-14JFE STEEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280098443.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-08-01
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In solid reduction furnaces, non-fired pellets are prone to pulverization and clustering at high temperatures, resulting in the inability to move and remove the pellets in the furnace, affecting the operating efficiency.

Method used

By increasing the proportion of highly viscous slag component (Al2O3+MgO+SiO2) in the non-sintered pellets, the proportion of its relative total iron reaches 0.12 or above, and high LOI raw materials are used during the manufacturing process to reduce the crystallization water content to form porous pellets.

Benefits of technology

It effectively prevents contact and fusion between the slag, reduces the occurrence of clustering phenomena, improves the operating efficiency of the solid reduction furnace, and reduces CO2 emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630820A_ABST
    Figure CN119630820A_ABST
Patent Text Reader

Abstract

Provided are an unfired pellet and a method for producing the same, the unfired pellet being effective for preventing clustering by preventing fusion by reducing the opportunity of contact between low-melting-point slag in the production of an unfired pellet used in a solid reduction furnace. The invention relates to an unfired pellet for reduction and a method for manufacturing the same. The ratio of the high-viscosity slag component (Al2O3 + MgO + SiO2) relative to the total Fe (T.Fe) in the unfired pellet for reduction satisfies the formula: (Al2O3 + MgO + SiO2) / T.Fe > = 0.12. Wherein Al2O3 is the component concentration (mass%) of Al2O3 in the unfired pellets, MgO is the component concentration (mass%) of MgO in the unfired pellets, SiO2 is the component concentration (mass%) of SiO2 in the unfired pellets, and T.Fe is the component concentration (mass%) of T.Fe in the unfired pellets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a non-fired pellet for reduction effective for a solid reduction furnace and a method for manufacturing the same. Background Art

[0002] In recent years, in order to avoid global warming caused by an increase in CO2, various technological developments for reducing its emissions have been underway. For example, in the field of the iron and steel industry, in a solid reduction furnace typified by a shaft furnace, non-fired pellets are mostly used. This is because, in the operation of ordinary fired pellets, CO2 is inevitably generated during the firing process. However, from the viewpoint of reducing CO2, this is not desirable, and the use of non-fired pellets has received attention.

[0003] Especially in the field of an iron-making method based on a solid reduction furnace as a hydrogen-based reduction process, research on non-fired pellets used in this method is underway. However, it is known that in the above-mentioned solid reduction furnace, when the charged raw material (non-fired pellet) passes through the high-temperature region in the furnace and the hematite phase in the pellet is reduced and changed to the magnetite phase, accompanied by volume expansion, a pulverization phenomenon occurs. In addition, it is known that in addition to the contact and fusion of metallic irons with each other, the contact and fusion of low-melting-point slags also occur. As a result, it is known that clustering occurs in the furnace and the pellets in the furnace cannot move, resulting in a scaffolding phenomenon where they cannot be taken out from the bottom of the furnace. Especially in a solid reduction furnace performing hydrogen-based reduction, this clustering is a very large problem to be solved.

[0004] Under such a background, several prior arts for the purpose of preventing clustering observed in the above-mentioned solid reduction furnace have been proposed in the past. For example, in Patent Document 1, a method of coating Ca(OH)2 and Mg(OH)2 on the pellet surface is proposed. In Patent Document 2, a method of preventing reduction pulverization and obtaining a fired pellet with little expansion by coating the surface of a fired lump ore (pellet) with a powdery solid fuel is proposed. In addition, in Patent Document 3, by coating the surface of a fired pellet with iron ore containing cement, clustering in a solid reduction furnace is prevented, and heat loss is reduced and operation efficiency is improved. In addition, in Patent Document 4, a technique of coating a substance containing a calcium iron compound formed by CaxFeyOz (1 < y / x ≤ 2; 1 ≤ z) is proposed.

[0005] Prior Art Documents

[0006] Patent Documents

[0007] Patent Document 1: Japanese Patent Laid-Open No. 59-10411

[0008] Patent Document 2: Japanese Patent Laid-Open No. 62-37325

[0009] Patent Document 3: Japanese Patent Application Laid-Open No. 63-262426

[0010] Patent Document 4: Japanese Patent Application Publication No. 2017-119910 Summary of the invention

[0011] Problems to be solved by the invention

[0012] The above-mentioned prior arts (Patent Documents 1-4) are all methods of reducing the contact between the reduced metallic irons, which is the cause of the clusters observed near the high temperature area (500-600°C) in a solid reduction furnace such as a shaft furnace, mainly by the presence of non-metallic components. However, according to the inventor's research, the cluster prevention methods of the above-mentioned prior arts are insufficient. In addition, for example, a coating process of non-metallic components needs to be separately adopted, which not only increases the cost, but also requires additional special equipment.

[0013] Therefore, an object of the present invention is to propose a non-calcined pellet and a method for producing the same, which is effective in preventing clustering by reducing the chance of contact between low-melting-point slags and preventing fusion during the production of non-calcined pellets used in a solid reduction furnace.

[0014] Means for solving problems

[0015] The present invention is a technology developed to solve the above-mentioned problems existing in the prior art and to achieve the above-mentioned objectives. First, a non-fired pellet for reduction is proposed, which is characterized in that the ratio of the high-viscosity slag component (Al2O3+MgO+SiO2) to the total Fe (T.Fe) satisfies the following formula (1).

[0016] remember

[0017] (Al2O3+MgO+SiO2) / T.Fe≥0.12···(1)

[0018] Wherein, Al2O3: Al2O3 component concentration in unfired pellets (mass %)

[0019] MgO: MgO content in unfired pellets (mass %)

[0020] SiO2: Concentration of SiO2 in unfired pellets (mass %)

[0021] T.Fe: T.Fe component concentration in unfired pellets (mass %)

[0022] Furthermore, secondly, the present invention provides a method for producing unburned pellets for reduction, characterized in that, in the production of the unburned pellets for reduction, a raw material blended so as to have an average LOI (loss on ignition) of 5% or more is used as the iron-containing raw material.

[0023] It should be noted that, for the aforementioned non-calcined pellets for reduction, the following scheme in the present invention is considered to provide a more preferred embodiment. That is,

[0024] (a) The ratio of the high viscosity slag components (Al2O3+MgO+SiO2) to the total Fe (T.Fe) satisfies the following formula (2),

[0025] remember

[0026] (Al2O3+MgO+SiO2) / T.Fe≥0.15···(2)

[0027] Wherein, Al2O3: Al2O3 component concentration in unfired pellets (mass %)

[0028] MgO: MgO content in unfired pellets (mass %)

[0029] SiO2: Concentration of SiO2 in unfired pellets (mass %)

[0030] T.Fe: T.Fe component concentration in unfired pellets (mass %)

[0031] In addition, in the production of non-calcined pellets for reduction,

[0032] (b) the iron-containing raw material is a raw material that has been pre-treated to remove water of crystallization so that the average LOI (loss on ignition) is 2% or less.

[0033] (c) mixing raw materials containing M.Fe to prepare a mixed raw material containing 4 mass % or more and 24 mass % or less of M.Fe, and granulating the mixed raw material,

[0034] (d) the raw material is reduced iron having a particle size of 3 mm or less which is reduced in a solid reduction furnace,

[0035] (e) The reduced iron contains 79 mass % or more of M.Fe.

[0036] M.Fe represents metallic iron, and the same shall apply hereinafter.

[0037] Effects of the Invention

[0038] The non-fired pellets for reduction of the present invention according to the above-mentioned constitution do not have a firing process, so they are preferred from the viewpoint of not generating CO2 and reducing CO2. In particular, by containing a relatively large amount of high-viscosity slag components (Al2O3, MgO, SiO2) relative to the total iron, the generation of low-melting-point slag caused by FeO in the solid reduction furnace and its fluidity can be reduced. As a result, the chance of contact and fusion between pellets caused by the presence of such slag can be prevented, and the above-mentioned clusters in the reduction furnace, which is a problem, can be effectively prevented.

[0039] In addition, according to the manufacturing method of the present invention, by using a high LOI raw material as an iron-containing raw material, the obtained non-fired pellets can be made porous. As a result, the chance of contact between metallic irons can be reduced, so clustering can be effectively prevented, and the operating efficiency of the solid reduction furnace can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] [ Figure 1 ] is a graph showing the relationship between (Al2O3+MgO+SiO2) / T.Fe and LOI for Australian iron ore used as an iron-containing raw material. DETAILED DESCRIPTION

[0041] The solid reduction furnace used in the present invention is a furnace for using hydrogen or the like as a reducing gas, charging unburned pellets for reduction into the furnace, and reducing them to a reduction rate of 90% or more of Fe. In the operation of the solid reduction furnace, the properties of the raw material charged into the furnace, i.e., the unburned pellets, are important.

[0042] As for the non-fired pellets, the most important thing is whether it is possible to prevent the clustering caused by the contact and mutual fusion of the pellets in the high temperature area (500-800°C) in the aforementioned solid reduction furnace. In response to such a requirement, the present invention studies the relationship between iron-containing raw materials such as metallic iron, i.e., iron oxides such as iron ore, iron sulfide, and ironmaking dust, and high-viscosity slag components, i.e., viscous components. The results show that from the perspective of the fluidity of the raw materials in the furnace, it is ideal to properly manage the relationship with the high-viscosity slag components. That is, by always producing high-viscosity slag in the furnace, undesirable flow in the high-temperature area is suppressed. In this way, the fusion of slags can be prevented, and clustering can be prevented.

[0043] As described above, it is found that in the present invention, it is effective to include a high-viscosity slag component at a certain ratio in the iron-containing raw material, iron ore, or auxiliary raw materials to be blended.

[0044] As components that can become the high-viscosity slag, special attention is paid to (Al2O3, MgO, SiO2). When their total amount maintains a specified ratio relative to the total iron (T.Fe), the fusion of the aforementioned slags generated in the furnace can be effectively prevented.

[0045] This can be achieved by making the composition of the unburned pellets for reduction contain the aforementioned high viscosity slag component (Al2O3+MgO+SiO2) at a certain ratio relative to the total iron (T.Fe) in the iron-containing raw material. That is, the unburned pellets are made to satisfy the relationship of the following formula (1).

[0046] remember

[0047] (Al2O3+MgO+SiO2) / T.Fe≥0.12···(1)

[0048] In the above formula (1), Al2O3 is the component concentration (mass %) of Al2O3 in the aforementioned non-fired pellets for reduction. MgO is the component concentration (mass %) of MgO in the aforementioned non-fired pellets for reduction. SiO2 is the component concentration (mass %) of MgO in the aforementioned non-fired pellets for reduction. T.Fe is the total Fe concentration (mass %) of the aforementioned non-fired pellets for reduction.

[0049] In the present invention, from the viewpoint of preventing contact and fusion of slags in the high temperature region of the furnace, the aforementioned high viscosity slag component (Al2O3+MgO+SiO2) and total iron (T.Fe) have a more preferable relationship. That is, as shown in the following formula (2) containing a larger amount of high viscosity slag components.

[0050] remember

[0051] (Al2O3+MgO+SiO2) / T.Fe≥0.15···(2)

[0052] In the above formula (2), Al2O3 is the component concentration (mass %) of Al2O3 in the aforementioned non-fired pellets for reduction. MgO is the component concentration (mass %) of MgO in the aforementioned non-fired pellets for reduction. SiO2 is the component concentration (mass %) of MgO in the aforementioned non-fired pellets for reduction. T.Fe is the total Fe concentration (mass %) of the aforementioned non-fired pellets for reduction.

[0053] It should be noted that, in the present invention, the total Fe in the iron-containing raw material refers to the total value of the iron content concentration of iron compounds (iron oxide, iron sulfide, calcium ferrite, etc.) in addition to metallic iron (M.Fe). On the other hand, the high-viscosity slag component refers to the total value of the Al2O3 concentration, MgO concentration, and SiO2 concentration contained in the auxiliary raw materials (limestone, quicklime, dolomite, etc.) and the binder (bentonite, etc.) in addition to the iron-containing raw materials such as iron ore and ironmaking dust.

[0054] The aforementioned Al2O3 concentration, MgO concentration, and SiO2 concentration can be calculated as follows. First, the Al concentration, Mg concentration, and Si concentration are measured by elemental analysis such as fluorescent X-rays. Then, the concentration of each element can be calculated by multiplying (molecular weight / atomic weight of the oxide corresponding to each unit of the element). Specifically, for example, the Al2O3 concentration can be calculated by multiplying the Al concentration measured by elemental analysis such as fluorescent X-rays by (Al2O3 molecular weight / 2) / Al atomic weight=50.98 / 26.98=1.890.

[0055] Next, the method for producing the non-fired pellets according to the present invention is described. In the production of the non-fired pellets for reduction according to the present invention, in order to achieve the above-mentioned relationship between the slag components (Al2O3+MgO+SiO2) and the total iron (T.Fe) of the obtained non-fired pellets with high viscosity, for example, the following combination can be considered, wherein one or more iron ores originally having the above-mentioned relationship are selected and used to combine and use two or more iron ores showing the above-mentioned relationship. For example, combining the iron ore produced in Australia such as Figure 1 One or more of the iron ores (A to Z) shown above are added with a binder such as bentonite and quicklime, and auxiliary materials as required, and granulation is performed.

[0056] In the aspect of charging the aforementioned non-calcined pellets into a solid reduction furnace for reduction, it is important that the aforementioned clusters are not formed in the high-temperature reducing atmosphere in the furnace. For this reason, in the present invention, LOI (Loss on Ignition) is particularly focused and its suitability value is studied. That is, in the production method according to the present invention, the aforementioned LOI (Loss on Ignition) value is made 5% or more, and the following is made: Figure 1 Some of the iron ores (A to Z) shown are selected and used (blended) to satisfy the LOI ≥ 5%. This can more effectively reduce clusters. This is because when volatile components such as crystal water are heated in the reduction furnace and dissociate and gasify and then dissipate outside the pellets, the volume of the mineral phase remaining in the pellets shrinks, and gaps are generated between the mineral phases.

[0057] Next, in the production method of the present invention, in order to achieve the above-mentioned LOI ≥ 5% as the iron-containing raw material, it is preferred to perform a pretreatment such as a de-crystallization water treatment on the iron ore used so as to achieve LOI ≤ 2%. This is because the iron-containing raw materials such as raw iron ore often contain a large amount of crystal water, and therefore, during granulation, the water vapor generated by the crystal water often causes the pellets to break. Therefore, the temperature has to be raised slowly.

[0058] Moreover, it hinders productivity.

[0059] [Example]

[0060] <Example 1>

[0061] This embodiment (including comparative examples) clearly shows how the relationship between T.Fe of the non-fired pellets for reduction and the highly viscous slag components (Al2O3+MgO+SiO2) affects the clusters in the solid reduction furnace.

[0062] For the iron-containing raw materials used in the implementation, namely iron ore, the main materials used are as follows: Figure 1 One or more of the Australian iron ores shown above, and auxiliary materials and reagents (such as commercially available Al2O3 reagents) are blended as needed. Table 1 shows the blending examples.

[0063] 5 mass % of cement was added to obtain a predetermined composition, and then the mixture was pulverized by a ball mill, granulated into 9 to 16 mm granules by a granulator while adding water, and then cured for 2 weeks to produce non-calcined pellets.

[0064] A ball mill was used to grind one or more of the above Australian raw materials (for example, Figure 1 All raw materials involved in the formulation shown in Table 1 are crushed, and then granulated into 9 to 16 mm in size while adding water using a granulator. The obtained granulated non-fired pellets are cured for 2 weeks to obtain non-fired pellets. The obtained non-fired pellets shown in Table 1 are evaluated using the cluster index.

[0065] (Cluster evaluation test)

[0066] 500g of sample was placed in a 100mmφ vertical cylindrical furnace and heated to 1000℃ in a N2 atmosphere. After reaching 1000℃, reducing gas was introduced at 24NL / min. The composition of the reducing gas was H2:N2=20:80 by volume. 2The sample is loaded and kept for 3 hours, and then cooled in a N2 atmosphere to produce reduced iron. Then, the obtained reduced iron is sieved with 16 mm, which is the maximum size of the non-sintered pellet monomer, and the weight of the sieve Wa (g) is measured. Then, the sieve is placed in a cylindrical container (132 mmφ×700 mmL) of a type I testing machine, rotated at a rotation speed of 30 rpm for 5 minutes, and then sieved with 16 mm to measure the weight of the sieve Wb (g). Then, it is evaluated as a cluster index proportional to the ratio of unbroken clusters Wb / Wa.

[0067] The porosity of the fired pellets was evaluated by measuring the true density after measuring the apparent density. As shown in Table 1, the cluster index of Examples 1 to 6, in which (Al2O3+MgO+SiO2) / T.Fe was 0.12 or more, was confirmed to be 15 or less, and the fired pellets had good properties.

[0068] [Table 1]

[0069]

[0070] In addition, the component composition of the uncalcined pellets obtained in Examples 1 and 2 in Table 1 is shown in Table 2 below.

[0071] [Table 2]

[0072] (quality%)

[0073] T.Fe FeO <![CDATA[SiO2]]> CaO <![CDATA[Al2O3]]> MgO C / S Example 1 59.9 0.2 4.1 4.4 2.7 0.6 0.4 Example 2 57.7 0.4 5.8 6.0 2.3 0.5 0.6

[0074] <Example 2>

[0075] Reduced iron (sample at the time of measuring Wa) obtained by the same method as that of Comparative Example 2 shown in Table 1 (cluster evaluation test) of Example 1 was pulverized, and the reduced iron with a particle size of 3 mm or less was mixed with the raw material before calcination of Comparative Example 2, and uncalcined pellets were produced using the method of Example 1. The crushing strength of the uncalcined pellets after 2-week curing was measured.

[0076] The results are shown in Table 3 below. "M.Fe" in Table 3 is derived from metallic iron (M.Fe) contained in reduced iron. Examples 10 to 12 used reduced iron with M.Fe = 78% by mass, and Example 13 used reduced iron with M.Fe = 80% by mass. As a result, it can be seen that the strength of the pellets is improved by mixing M.Fe into the raw materials. Since clustering is promoted by the increase in powder, clustering can be suppressed by increasing the strength of the non-fired pellets. In addition, it is believed that the reason why the strength of the non-fired pellets is improved by adding M.Fe to the raw materials is that the air comes into contact with the reduced iron powder during the curing period, and the metallic iron oxidizes and generates heat, so that the bonding between adjacent particles is promoted. Therefore, the effect of improving the strength of the non-fired pellets by adding M.Fe to the raw materials begins to appear 2 days after granulation, and the increase in strength almost stops 4 weeks after granulation.

[0077] [Table 3]

[0078]

[0079] In this specification, L as a volume unit means 10 -3 m 3 The symbol "N" attached to the volume unit of gas indicates the volume of gas at 0°C and 101325 Pa as the standard state. The unit of rotation speed rpm indicates the number of rotations per minute.

[0080] Industrial Applicability

[0081] The solid reduced non-calcined pellets according to the present invention are technologies developed mainly for application to hydrogen-based direct reduction processes and the like, and can of course also be used as a raw material used in blast furnaces and the like.

Claims

1. Non-fired pellets for reduction, characterized in that: The ratio of the high viscosity slag components (Al2O3+MgO+SiO2) to the total Fe (T.Fe) satisfies the following formula (1): (Al2O3+MgO+SiO2) / T.Fe≥0.12···(1) Wherein, Al2O3: Al2O3 component concentration in unfired pellets (mass %) MgO: MgO content in unfired pellets (mass %) SiO2: Concentration of SiO2 in unfired pellets (mass %) T.Fe: The T.Fe component concentration (mass %) in the uncalcined pellets.

2. Non-calcined pellets for reduction, characterized in that: The ratio of the high viscosity slag components (Al2O3+MgO+SiO2) to the total Fe (T.Fe) satisfies the following formula (2): (Al2O3+MgO+SiO2) / T.Fe≥0.15···(2) Wherein, Al2O3: Al2O3 component concentration in unfired pellets (mass %) MgO: MgO content in unfired pellets (mass %) SiO2: Concentration of SiO2 in unfired pellets (mass %) T.Fe: The T.Fe component concentration (mass %) in the uncalcined pellets.

3. A method for producing non-calcined pellets for reduction, characterized in that: In the production of the non-calcined pellets for reduction according to claim 1 or 2, a raw material blended so as to have an average LOI (loss on ignition) of 5% or more is used as the iron-containing raw material.

4. The method for producing non-calcined pellets for reduction according to claim 3, wherein: The iron-containing raw material used was a raw material that had been pre-treated in advance to remove water of crystallization so that the average LOI (loss on ignition) was 2% or less.

5. A method for producing non-calcined pellets for reduction, characterized in that: A raw material containing M.Fe is blended to prepare a mixed raw material containing 4 mass % to 24 mass % of M.Fe, and the mixed raw material is granulated.

6. The method for producing non-calcined pellets for reduction according to claim 5, wherein: The raw material is reduced iron with a particle size of less than 3 mm that is reduced in a solid reduction furnace.

7. The method for producing non-calcined pellets for reduction according to claim 6, wherein: The reduced iron contains 79 mass % or more of M.Fe.

Citation Information

Patent Citations

  • Controlling device of wall thickness in mandrel mill

    JP1984010411A

  • Calcined lump ore and its production

    JP1987037325A

  • Raw material for iron manufacture

    JP1988262426A

  • Reduction raw material, and method for producing reduction raw material

    JP2017119910A